2004
DOI: 10.1158/1055-9965.epi-270-2
|View full text |Cite
|
Sign up to set email alerts
|

Relative Validity of a Food Frequency Questionnaire with a Meat-Cooking and Heterocyclic Amine Module

Abstract: The nutrient and heterocyclic amine (HCA) intake of 165 healthy participants was assessed using a self-administered food frequency questionnaire (FFQ), which included a meatcooking practices module. A database containing the HCA IntroductionNumerous studies have demonstrated an association between red meat intake and the etiology of various cancers (1-8). A group of mutagenic and carcinogenic compounds called heterocyclic amines (HCAs), formed through pyrolysis of amino acids and creatine in meat using high t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 28 publications
2
58
1
Order By: Relevance
“…The relative validity of the meat module was similar to that of other nutrients and food quantified in FFQs (38,39). For example, the deattenuated correlations were 0.60 and 0.36 for 2-amino-3,4,8-trimethylimidazo [4,5-f]quinoxaline (DiMeIQx) and 2-amino-1-methyl-6-phenylimidazo [4,5-b]pyridine (PhIP), respectively (37).…”
Section: Methodsmentioning
confidence: 70%
See 2 more Smart Citations
“…The relative validity of the meat module was similar to that of other nutrients and food quantified in FFQs (38,39). For example, the deattenuated correlations were 0.60 and 0.36 for 2-amino-3,4,8-trimethylimidazo [4,5-f]quinoxaline (DiMeIQx) and 2-amino-1-methyl-6-phenylimidazo [4,5-b]pyridine (PhIP), respectively (37).…”
Section: Methodsmentioning
confidence: 70%
“…A formal validation study for the meat-mutagen data has not been conducted within the NIH-AARP study cohort. The validity of the meat intake, meat-cooking methods, and doneness, as well as meat-derived mutagens, however, was assessed in a U.S. population of 165 healthy subjects who completed an FFQ that included the meat module and three sets of four nonconsecutive day diaries (37). Correlations were computed for intake between the two methods of dietary assessment (37).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FFQ that we used did not query participants on several parameters that influence BaP levels in meat, such as distinguishing between beef and hamburger consumption when asking about intake of red meat. Cantwell et al (2004) also found that the FFQ underestimates beefsteak, pork, sausage, and grilled/bbq chicken intake. Also, our results are based on a measure of PAH-DNA adducts assessed in peripheral mononuclear cells which have a short lifetime (Tuominen et al, 2002), yet our measure of grilled and smoked food reflected intake over the current decade of life.…”
Section: Discussionmentioning
confidence: 87%
“…This is a costly undertaking, which currently is beyond our capacity. However, the high validity of the MDC dietary data and of the analytical data makes this 38 . They found that the FFQ gave lower estimated intakes of MeIQx and PhIP.…”
Section: Discussionmentioning
confidence: 99%